Hubungan tabungan-pelaburan dan analisis mobiliti modal - Jauhari, Azmafazilah; Mohammed, Nafisah (Universiti Utara Malaysia, 2005)
This article examines the relationship between the saving-investment correlation and the degree of capital mobility of the Asian countries: Malaysia,Singapore, Thailand, India, Indonesia, Myanmar, Pakistan, China, Hong Kong, Korea, Philippines, Japan, and Sri Lanka over the period 1960 to 2000. Open macroeconomic model and Overlapping Generation (OLG) model, was used as the theoretical framework. Specifically, objectives of this research are to evaluate the long-run and short-run dynamic relationship between saving and investment rates using the Vector Error Correction Mechanism (VECM) and impulse response function. For policy implication, Granger causality test was applied to examine whether the growth of saving rates affects the growth of investment, or the growth of investment, rates causes the growth of saving rates. The results for VECM show that saving and investment rates for China, Philippines, Korea, Malaysia, Pakistan and Singapore are cointegrated. This suggests that there exist the long-run relationship for both variables in those countries. Results also show that the growth of saving rates affects the growth of investment for Philippines and Singapore. The reverse causality holds for China and Indonesia. However, for Japan, Korea and Myanmar there exist the causality flows both ways.